3D simulation of transport phenomena of onion drying with moving boundary in a vacuum oven. (3rd January 2020) - Demir, Hasan; Cihan, Ertuğrul; Demir, Hande
Abstract: This study aimed to perform numerical simulation of the onion drying process considering its deformed geometry. For this purpose, transport phenomena such as heat and mass transfer in the onion structure and water vapor transfer in its porous structure were simulated in 3D form with Darcy's law during the vacuum drying process for onions. The simulated results were validated by experimental data. Heat and mass transfer rates were determined using kinetic data. Simulation of onion drying revealed that deformed geometry should be included in the model to represent the faster removal of water from the onion due to the increase in mass transfer surface area. The influence of drying temperature (313, 323, 333, and 343 K) on drying time and water concentration of onion was insignificant. The mass transfer Biot number revealed that the water vapor removal from onion was controlled by intraparticle mass transfer resistance. Practical applications: The main purpose of the vegetable drying industry is to obtain good‐quality dried products accompanied by savings in terms of energy and time. Recently, heat and mass transfer models constructed for drying of vegetables have focused on vegetables such as potato or carrot that provide limited information due to their uniform structure. An onion slice has a porous structure and increasing spaces between its rings; therefore in this study, heat and mass transfer occurring during vacuum drying of an onion was simulated considering the deformed geometry. The analysis of transport phenomenon mechanisms involves valuable information for researchers studying drying of food and large‐scale vacuum dryer designers in which 3D simulation of onion drying revealed that the deformed geometry fitted better to experimental results than undeformed geometry. The results of 3D simulation can be used to predict drying time and energy requirements of the process better than regular numerical modeling and may serve dried onion manufacturers. Abstract :